Tinjauan Yuridis Terhadap Penyusunan APBD Kota Pekanbaru Tahun 2015 - Rialdo Putra; Dodi Haryono; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Problems budgeting in attestation Pekanbaru City budget in 2015, it was the intervention of Parliament too strong budget right where legislators often propose activities that stray away from the proposed community planning forums. Recess schedule of Parliament with Musrenbang process that does not match Musrenbang already done, the new parliament recess resulted in many proposals of Parliament which then appears and changes the results Musrenbang. This legislative intervention based on the possibility of political motives for seeking the interests of constituent support so that legislators act like Santa Claus which divide the project.This study using sociological juridical approach. Sociological juridical research or empirical research approach is to look at in terms of the fact that occur in the field. While the descriptive nature of the research is aimed at providing a clear picture of the issues examined.The results of this study are: First, the district chief submitted a draft regional regulation on accountability of the budget to Parliament no later than 6 (six) months after the fiscal year ends, while the joint approval of the draft local regulations meant most lambat1 (one) month after the draft local regulations accepted by parliament. Implementation of the Fiscal Year 2015 budget changes must be made after the establishment of local regulations on accountability of the budget for Fiscal Year 2014 and the agreement between the regional government and parliament to draft local regulations on Amendment Fiscal Year 2015 budget is set at the latest by the end of September 2015. Second, Budgeting Pekanbaru city Fiscal year 2015 has been delayed due to new ratifications held in June of the fiscal year running. In the drafting process has been delayed due to the relationship the Executive to the Legislature responsible for the budget process Pekanbaru City Fiscal Year 2015 is less harmonious led to discussion of budget to be blocked, so that the determination of what must be done one month before the fiscal year can only be set by June 2015 or six months into the current fiscal year. In addition to these factors, delays in the preparation process is also influenced by political communication, leadership Regional Head, and Political CorruptionKey Word : Preparation - Budgets - Pekanbaru